Type Classification of Sudden Stratospheric Warming Based on Pre- and Postwarming Periods - Choi, Hyesun; Kim, Baek-Min; Choi, Wookap (Journal of Climate, 2020)
In existing literature, sudden stratospheric warming (SSW) events have been typically defined as displacement or split types. Detailed reexamination of SSW evolution has revealed that an SSW event often alters its type before and after the central day of the warming event. On the basis of this observation, we objectively define three types of SSW using wave amplitude: displacement-displacement (DD) type, displacement-split (DS) type, and split-split (SS) type. The geopotential height (GPH) amplitude of zonal wavenumbers 1 and 2 averaged over 55 degrees-65 degrees N at 10 hPa was used as a criterion for the classification. If the amplitude of zonal wavenumber 1 is larger (smaller) than that of wavenumber 2 before and after the central day of SSW, the event is regarded as a DD (SS) type. If the amplitude of zonal wavenumber 1 is larger than that of wavenumber 2 before the central day but is smaller after that day, the event is regarded as a DS type. The above classification algorithm has been applied to both reanalysis data and model results. We observe that conventional split-type SSW events identified by previous studies can be categorized as either DS- or SS-type events, each type of which exhibits different evolution characteristics. In particular, they are distinctively different during the prewarming period. In the SS type, the characteristics of the conventional split type are more obvious, and the features that differ from those of the DD type are the most robust. The model results generally resemble the reanalysis data, particularly in the DD cases. N 1